Prediction of the rate of progression of primary open-angle glaucoma depending on gender and polymorphism of the endothelial NO-synthase (NOS3) gene - O.A. Isaiev; V.M. Serdiuk (Medičnì Perspektivi)
Relevance – it is promising to develop a system for the diagnosis and prevention of primary open-angle glaucoma (POAG), which would be based on the determination of constitutive propensity factors and would be able to predict the onset and progression of the disease. The aim of the study was to develop a model for predicting the rate of progression of primary open-angle glaucoma depending on gender and endothelial NO-synthase (NOS3) gene polymorphism. There were genotyped 153 patients with POAG aged 36-84 years. Genotypes rs1799983 and rs207074 were determined in the blood of patients by real-time polymerase chain reaction (amplifier Gene Amp® PCR System 7500; USA) using the TaqMan Mutation Detection Assays Life-Technology test system (USA). For mathematical processing of the obtained results, the Statistica 10 program (StatSoft, Inc., USA) was used. The rate of progression of POAG was higher in the presence of risk alleles in the haplotype of the NOS3 gene polymorphisms: T rs1799983 and C rs2070744 (haplotypes TT-CC, GT-CC and GT-CT), which, when distributed by gender, was more pronounced in women than in men of each of the possible haplotypes. The maximum difference was noted for carriers of the TT-SS haplotype, in whom the rate of progression of POAG in women exceeded that in men by 1.4 times (p<0.001). A regression model was built with satisfactory prediction indicators (multiple correlation coefficient R=0.963; coefficient of determination R2=0.928; p<0.001). The probable “hereditary” age of patients in which one or another stage of POAG should be expected is calculated. Gender and haplotypes rs1799983 and rs2070744 of the NOS3 gene were shown to be associated with the onset and rate of progression of POAG, which was implemented in the prognostic model of the disease. Separately for men and women, carriers of different haplotypes, the rate of progression and the possible age of POAG development by stages were calculated.